2017
DOI: 10.1536/ihj.16-617
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Current Evidence on the Impact of the Initial High Dose of the Direct Factor Xa Inhibitor Rivaroxaban on Thrombus Resolution in the Treatment of Venous Thromboembolism

Abstract: SummaryIncomplete thrombus resolution in patients with venous thromboembolism (VTE) may increase the risk of recurrent thromboembolic events and other complications, such as post-thrombotic syndrome. Various options exist for thrombus resolution, including systemic thrombolytic agents, catheter-directed thrombolysis, and traditional anticoagulants such as heparins or vitamin K antagonists (VKAs). Data are accumulating on the use of non-VKA oral anticoagulants, such as rivaroxaban, and these may provide greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Patients who underwent valve replacement required oral anticoagulant therapy because of the interaction of blood with the surface material of valve prostheses and nonphysiological blood flow. An appropriate intensity of anticoagulation should be achieved to reduce thromboem- Previous studies have suggested a low anticoagulation intensity with a target INR of 1.5-2.5 for Chinese patients post-MHVR, because the standard intensity may cause more bleeding in Chinese patients than in their Caucasian counterparts 2,13,14) owing to the polymorphism of the hemostatic gene and differences in factor levels, endothelial markers, platelet reactivity, and thrombolytic status. [15][16][17] On the basis of the above findings, a target INR range of 1.8-3.5 was used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who underwent valve replacement required oral anticoagulant therapy because of the interaction of blood with the surface material of valve prostheses and nonphysiological blood flow. An appropriate intensity of anticoagulation should be achieved to reduce thromboem- Previous studies have suggested a low anticoagulation intensity with a target INR of 1.5-2.5 for Chinese patients post-MHVR, because the standard intensity may cause more bleeding in Chinese patients than in their Caucasian counterparts 2,13,14) owing to the polymorphism of the hemostatic gene and differences in factor levels, endothelial markers, platelet reactivity, and thrombolytic status. [15][16][17] On the basis of the above findings, a target INR range of 1.8-3.5 was used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, reports describing its efficacy and postoperative safety assessment after spinal surgery are rare. The use of rivaroxaban, a factor Xa inhibitor, a direct thrombin inhibitor, to prevent VTE after joint replacement surgery has been evaluated in several Phase III clinical trials [ 10 ]. Apixaban, a highly specific factor Xa inhibitor, is administered as a twice daily fixed dose and does not require routine laboratory monitoring.…”
Section: Discussionmentioning
confidence: 99%